Factors Affecting Students’ Speaking Proficiency: Perspective from English Pre-service Teachers Teaching in southern Thailand - Rachmawati Nur, Maulidia; Isrina Septiana (JADEs Journal of Academia in English Education, 2025)
To create teaching speaking strategies, English teachers need to understand the factors affecting the oral proficiency of learners which should worhty of attention. This study aimed to investigate what the factors affecting students’ speaking proficiency based on perspective from English pre-service teachers while teaching in Thailand. The participants were three pre-service English teachers who had done teaching practicum in southern Thailand for four months. They taught at same level which was secondary level especially upper secondary level on EFL students. Questionnaire and semi-structured interview were used as research instruments. Thematic analysis was employed in the analysis of the data gathered from the teachers. The finding revealed that some of factors affecting students’ speaking proficiency based on pre-service teachers perspective are Cognitive, Linguistic and Affective factors.